Modulating the fatty acid composition of black soldier fly larvae via substrate fermentation - F. IJdema; S. Lievens; R. Smets; G. Poma; M. Van Der Borght; B. Lievens; J. De Smet (Animal)
Black soldier fly larvae (BSFL, Hermetia illucens) contain high amounts of proteins and essential amino acids and are therefore an appropriate feed source. However, they lack essential fatty acids (FAs), specifically ω-3 and ω-6, making them a less desirable feed choice for aquaculture. The aim of this study was to increase the ω-3 and ω-6 FA concentrations in BSFL by manipulating the FA composition in their rearing substrate. Specifically, the potential of substrate fermentation using the ω-3 and ω-6 FA−producing fungus Mortierella alpina was assessed. Fermentation of two agricultural side streams (wheat bran (WB) and WB with distiller’s dried grains with solubles (DDGS)) increased substrate total crude fat concentration by 2.1 – 4.6%, as well as the concentration of several essential FAs, including the ω-6 FAs arachidonic acid (from less than 0.2 mg/g fat to a maximum of 44.2 mg/g fat) and gamma-linolenic acid (from less than 1.2 mg/g fat to a maximum of 45.8 mg/g fat and the ω-3 FA eicosapentaenoic acid (EPA) (from less than 0.7 mg/g fat to a maximum of 49.9 mg/g fat). Rearing BSFL on feeds from such fermented substrates resulted in similar changes in larval FA composition, specifically a higher concentration of EPA (from less than 0.2 mg/g fat to a maximum of 26.6 mg/g fat in the larvae fed on fermented diets), however, larval growth was reduced. Feeds made from fermented substrates were prone to stickiness and dehydration, possibly limiting larval movement and feeding, thereby affecting larval growth. Furthermore, proximate analysis of the substrates revealed sugar depletion after fermentation, which could be detrimental for larval growth and illustrate important attention points going forward. This study shows that fermentation of agricultural side streams WB and a mixture of WB with DDGS with Mortierella alpina alters their FA profile, increasing their ω-3 and ω-6 FA concentrations and that of BSFL fed with those substrates. Therefore, these results suggest that BSFL with tailor-made FA profiles for a specific application could be successfully produced.